National sovereignty in the political doctrine of Front National/Rassemblement National - Wielomski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The Étatnation (Nation-State) doctrine is the main ideology of the French Revolution and subsequent revolutionary tradition, but the contemporary French left and liberal centre are pro-Europeans and hostiles to idea of Nation-State. The whole spectrum of French political elite reject the idea of nation and Nation-State as “reactionary” and “undemocratic”. In France, the idea of État-nation is defended by the nationalist right only, symbolised by the Le Pen’s family. The purpose of this text is to present this genetically-leftist idea as the programme of the political right.
Keywords: Le Pen, Jean-Marie (1928-2025); Le Pen, Marie (1968-); Front Narodowy; Zjednoczenie Narodowe; nacjonalizm